Correlation between Forced Expiratory Volume One Second and Vital Capacity with VO2 Maximum - Rahmania, Siti Khadijah; Prabowo, Tertianto; Tessa, Putri (Althea Medical Journal, 2016)
Background: Medical students need to cope with their tight schedule, which also demand a good physical fitness to do those activities. Insufficient leisure time and exhausting activities impede studentsâ capacity on having routine physical exercise to maintain their physical fitness. Cardiopulmonary endurance describes a person physical fitness level, and lung function is one basic component of cardiopulmonary endurance. Without optimal lung function, circulatory system in the body cannot work properly. This study aimed to determine whether lung function giving a significant correlation with the cardiorespiratory endurance which are measured by Forced Expiratory Volume One Second (FEV1), Vital Capacity (VC), and VO2Maximum (VO2max), respectively.Methods: This study was conducted in SeptemberâOctober 2013 to the students of Faculty of Medicine at Universitas Padjadjaran academic year 2010â2012, using the cross-sectional method. Sample was taken through simple random sampling process. There were 34 male and 34 female students after controlling for covariates. Direct measurement using spirometer used to determine lung function and maximum oxygen uptake was measured by assessing Rhyming Step Test result. Correlation coefficient was then calculated by Pearson correlation test.Results: The correlation between FEV1with VO2max of male students giving a value of p=0.442, while for VC obtained a value of p=0.259. Female students result giving a value of p=0.746 for the FEV1with VO2max, and p=0.489 for the VC with the VO2max.Conclusions: There is no significant correlation between FEV1 and VC with the VO2max of the respondents. [AMJ.2016;3(3):430â3]Â DOI: 10.15850/amj.v3n3.868